Pola Manajemen Partisipatif sebagai Upaya Pengembangan Prestasi di MTs Muhammadiyah Karangkajen Yogyakarta (Proceeding Annual Conference on Madrasah Teacher, 2022)
The article entitled Participatory Management Patterns as Achievement Efforts at MTs Muhammadiyah Karangkajen Yogyakarta aims to 1. Know the new input raw input strategy 2. Knowing strategies for improving human resources 3. Knowing ways to improve student achievement 4. Knowing the efforts to complete madrasa infrastructure. The method used to explore practical experience as the head of MTs Muh. Karangkajen for five years. The strategies used to achieve the objectives are 1. Collaboration with the principal in the neighborhood, the head of the Yogyakarta City MTs and the Gondowulung State MTs. 2. Giving motivation to teachers and employees with a future orientation. 3 Provision of motivation and stabilizing the implementation of teaching and learning 4. Collaboration with madrasah committees, communities, government and related institutions. The strategies that have been carried out so far are 1. Collaboration with principals of primary schools and MTs in the surrounding environment including a. Preparation, formation of PPDB implementation team, making brochures, and pamphlets b. Prospective student data c. Division of officers from madrasas d. Schedule a visit to elementary school in the surrounding environment. 2. Motivation for teachers and employees with future orientation includes a. Awarding is adjusted to the needs of the human resources as well as the conditions of the madrasah b. Briefing on improving teacher quality c. Explanation of expected achievements d. Adjust teacher characteristics 3. Provision of motivation and strengthen the implementation of KBM include a. Establishment of an achievement motivation training team. B. Prepare activity proposals c. Setting the implementation schedule d. Participatory approach. 4. Collaboration with madrasah committees, communities, government is to encourage parents and the community to participate in the provision of infrastructure. From the above strategies, it was obtained the results of increasing public interest to include their children in the Muhammadiyah Karangkajen MTs, increased teacher and employee HR, student achievement increased from year to year and the addition of adequate infrastructure.